Mensageiros secundários relacionados à ação dos hormônios vegetais - Inácio, Marielle Cascaes [UNESP]; Silva, Edvar de Sousa da [UNESP]; Souza, Manoel Euzébio de [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (My University, 2011)
The current knowledge about the mechanisms of action of plant hormones is still fragmented and incomplete. However, it’s known that the regulatory action and that the potential of signal amplification of these molecules occurs through the process of translation of signals initiated from the binding of hormones to their receptors. The formation of short life secondary messengers occurs due to the start of a chain of events resulting from the binding of plant hormone to its receptor. There are several secondary messengers, but each hormone, acting in a specific cell type triggers the appearance of secondary messengers, also specific. These second messengers include 1,2-diacylglycerol, inositol 1,4,5-triphosphate and calcium ions, among others.

Os conhecimentos atuais sobre os mecanismos de ação dos hormônios vegetais são ainda fragmentados e incompletos. No entanto, já se sabe que a ação reguladora e que o potencial de amplificação de sinais destas moléculas se dá através de vias de tradução de sinais iniciadas a partir da ligação dos hormônios aos seus receptores. A formação de mensageiros secundários de vida curta ocorre em função do início de uma cadeia de eventos resultante da ligação do hormônio vegetal ao seu receptor. Existem vários mensageiros secundários, mas cada hormônio, atuando num tipo celular específico, desencadeia o surgimento de mensageiros secundários também específicos. Estes mensageiros secundários incluem o 1,2-diacilglicerol, o inositol 1, 4,5-trifosfato e os íons cálcio, entre outros.
Secondary messengers related to the action of plant hormones
Keywords: Signal transduction; 1,2-diacylglycerol; Inositol 1,4,5-triphosphate; Calmodulin; Calcium; Transdução de sinais; 1,2-diacilglicerol; Inositol 1,4,5-trifosfato; Calmodulina; Cálcio